2018
DOI: 10.1111/ane.12947
|View full text |Cite
|
Sign up to set email alerts
|

Prescription and predictors of post-stroke antidepressant treatment: A population-based study

Abstract: Antidepressant treatment in this real-life clinical setting was common and initiated early, in almost half the treated patients within 14 days. Our results suggest that special focus should be given to the severe strokes as they may have a greater risk of requiring treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Similarly, in a recent study on 5070 consecutive first-ever ischemic stroke patients with a mean age of over 70 years [20], almost half of the previously untreated patients started antidepressant medication shortly after IS, the cumulative incidence of antidepressant treatment over 6 months post-stroke was 35%, and the most commonly prescribed antidepressants were SSRIs. Furthermore, in that study [20], increasing stroke severity was associated with a higher likelihood of newly prescribed antidepressant after stroke. Association between stroke severity and initiating PSAD was also found in young individuals in our study.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, in a recent study on 5070 consecutive first-ever ischemic stroke patients with a mean age of over 70 years [20], almost half of the previously untreated patients started antidepressant medication shortly after IS, the cumulative incidence of antidepressant treatment over 6 months post-stroke was 35%, and the most commonly prescribed antidepressants were SSRIs. Furthermore, in that study [20], increasing stroke severity was associated with a higher likelihood of newly prescribed antidepressant after stroke. Association between stroke severity and initiating PSAD was also found in young individuals in our study.…”
Section: Discussionmentioning
confidence: 86%
“…While this finding seems self-evident, no other study investigating the determinants of ADM use after stroke considered information about depression. 13,[36][37][38][39] Only 1 study explored if the application of a depression screening determined ADM use and found no association, with the restriction of only 6 out of 123 people with stroke being screened. 40 Furthermore, history of depression and previous use of ADM were predictors of current use, reflecting the "feedback loop" of past health status and health service use on future use, as formulated by Andersen's model.…”
Section: Antidepressant Medication (Adm)mentioning
confidence: 99%
“…These factors and outcomes have been rarely considered in previous studies, presumably because they are not easily accessible in register-based research. 8,13,36,38,45 Future studies should consider the indication and adequacy of treatment, the dynamic nature of unmet need, the differentiation between health status and need as well as self-perceived and professionally evaluated need. 14,49 The replication of these findings is necessary to elaborate on the time-dependency of age and self-efficacy in predicting service use and in order to inform public health strategies adequately.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Administrative registries that routinely collect data at a population level can be useful resources for studies of temporal trends in cerebrovascular disorders, [1][2][3][4][5] and in observational research focusing on the cause, treatment, and course of stroke. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Large clinical databases or medical registers anchored in well-defined populations can furthermore be a particularly attractive solution to the challenge of acquiring valid data over extended time-periods for relatively rare disorders such as intracerebral hemorrhage (ICH). 10,[21][22][23][24][25][26][27][28][29] However, to be useful data sources for epidemiologic research, registers must first provide data of sufficiently high quality.…”
Section: Introductionmentioning
confidence: 99%